2021
DOI: 10.15603/1982-8756/roc.v17n34p389-425
|View full text |Cite
|
Sign up to set email alerts
|

A Interferência do Marketing na Construção de Padrões de Beleza

Abstract: A imagem do corpo se modifica no decorrer do tempo e a relação com o corpo e o que é considerado belo permeia a nossa sociedade desde a antiguidade. O marketing, através da mídia com suas peças publicitárias e propagandas, transmite padrões de beleza e comportamento e influencia diretamente a sociedade. A construção da identidade de gênero feminino é construída pela história, cultura e relações sociais que o indivíduo forma pelas experiências e vivências desde o nascer para se tornar e se reconhecer como mulhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…By using Instagram daily, young people can trigger insecurities about their perception of their bodies. According to Vieira (2019), there are currently standards that categorise people, so it is crucial and almost mandatory that they look good and have a good body image. A study carried out in Brazil involving 212 female adolescents concluded that the use of social networks, especially Instagram, is associated with dissatisfaction with the body image of adolescents (Lira et al, 2017), which indicates the negative impact that this application has on the lives of young people, especially female adolescents.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…By using Instagram daily, young people can trigger insecurities about their perception of their bodies. According to Vieira (2019), there are currently standards that categorise people, so it is crucial and almost mandatory that they look good and have a good body image. A study carried out in Brazil involving 212 female adolescents concluded that the use of social networks, especially Instagram, is associated with dissatisfaction with the body image of adolescents (Lira et al, 2017), which indicates the negative impact that this application has on the lives of young people, especially female adolescents.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These users have made the platform their primary form of work and share their daily lives, from the clothes they wear to where they go. Digital influencers usually have a high profile and exert a great deal of influence over their followers, so they always try to highlight the most positive side of their personality and their lives in their posts, ending up showing a life and a way of behaving that is not entirely real and true, making young people unable to realise what is real and what is not (Vieira, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%